Post-industrial university towns and the triple helix concept: case studies of Bristol, Sheffield, Novosibirsk and Tomsk - Oplakanskaia, Renata Valerievna; Osmuk, Lyudmila Alekseevna; Pogorelskaya, Anastasia; Pomorina, Inna (Bulletin of Geography. Socio-economic Series, 2019)
The paper examines the role of universities in city development under the Triple Helix model through case studies of Russian and British cities. The cases of Bristol and Sheffield illustrate that the implementation of the Triple Helix model can be achieved through different approaches. In Bristol, universities reached beyond their campuses to create a ground for cooperation with partners. In Sheffield, there was a platform for interaction with partners using the brand of a top university. Meanwhile, the examples of Tomsk and Novosibirsk provide some evidence for the growing importance of universities in the innovative urban economy. The comparative analysis provides recommendations for Russian universities, whose application of the Triple Helix model is prevented by the lack of experience in developing an effective marketing strategy and weak interactions between research and enterprises.